高温酸沉对大豆分离蛋白品质的影响 Effect of high-temperature acid precipitation on the quality of soybean protein isolate - 时玉强1,2，马军1，李顺秀1，赵洪兵1，王兴煜1，郭增旺3 SHI Yuqiang1,2, MA Jun1, LI Shunxiu1, ZHAO Hongbing1, WANG Xingyu1, GUO Zengwang3 (Zhongguo youzhi, 2024)
为了拓宽大豆分离蛋白的应用范围，降低大豆分离蛋白中大豆异黄酮的含量，考察了高温酸沉对大豆分离蛋白品质的影响。分析了不同酸沉温度下，大豆分离蛋白中主要大豆异黄酮类物质含量的变化，大豆乳清中粗蛋白质含量及固形物含量的变化，大豆分离蛋白水合蓝光白度的变化，以及大豆分离蛋白凝胶值的变化。结果表明：酸沉温度从70 ℃升高到85 ℃，大豆异黄酮总量降低了43.84%，其中大豆苷、染料木苷含量分别降低了88.76%、83.95%，黄豆黄苷降到了检出限以下，而大豆苷元、染料木素含量分别提高了72.51%和143.47%，黄豆黄素的含量变化不显著；随酸沉温度升高，大豆乳清中的粗蛋白质含量和固形物含量不断降低，与酸沉温度70 ℃时相比，酸沉温度85 ℃时粗蛋白质含量降低了25.12%，固形物含量降低了6.34%；随酸沉温度升高，大豆分离蛋白的水合蓝光白度不断增加且增速不断提高，与酸沉温度70 ℃时相比，酸沉温度85 ℃时水合蓝光白度增加了26.83%；随酸沉温度升高，大豆分离蛋白的凝胶值不断降低，与酸沉温度70 ℃时相比，酸沉温度85 ℃时凝胶值降低了57.02%。综上，高温酸沉可有效控制大豆分离蛋白中大豆异黄酮的含量，提高大豆分离蛋白的水合蓝光白度和回收率，对开发低异黄酮含量的婴幼儿产品有积极意义。In order to broaden the application of soybean protein isolate(SPI) and reduce the content of soybean isoflavones in SPI, the effects of high-temperature acid precipitation on the quality of SPI were investigated. Under different acid precipitation temperatures, the changes of main soybean isoflavone content in SPI, the changes of the crude protein content and solid content in soybean whey, the changes of hydration blue brightness and gel value of SPI were analyzed. The results showed that the acid precipitation temperature increased from 70 ℃ to 85 ℃, the total amount of soybean isoflavones decreased by 43.84%, among which daidzin, genistin contents decreased by 88.76%, 83.95% respectively, and the content of glycitin dropped below the detection limit, whereas daidzein and genistein contents increased by 72.51% and 143.47% respectively, and the content of glycitein had no significant difference. The crude protein content and solid content in soybean whey decreased continuously with the increase of acid precipitation temperature. Compared with 70 ℃, at the acid precipitation temperature 85 ℃, the crude protein content in soybean whey decreased by 2512%, and the solid content decreased by 6.34%. With the increase of acid precipitation temperature, the hydration blue brightness of SPI continued to increase and the growth rate continued to increase, and the hydration blue brightness increased by 26.83%, when the temperature increased from 70 ℃ to 85 ℃. With the increase of acid precipitation temperature, the gel value of SPI decreased continuously, and it reduced by 57.02% when the acid precipitation temperature increased from 70 ℃ to 85 ℃. In conclusion,the high-temperature acid precipitation process could effectively control the soybean isoflavones content in SPI, improve the hydration blue brightness and recovery capacity of SPI, which is of positive significance for the development of infant products with low soybean isoflavones content.